Modified lignin from sugarcane bagasse as an emulsifier in oil-in-water nanoemulsions - Brenelli, Lívia Beatriz; Mariutti, Lilian Regina Barros; Villares Portugal, Rodrigo; de Farias, Marcelo Alexandre; Bragagnolo, Neura; Mercadante, Adriana Zerlotti; Franco, Telma Teixeira; Rabelo, Sarita Cândida [UNESP]; Squina, Fabio Marcio (Elsevier, 2021)
Lignin from pre-treated sugarcane bagasse was sulfomethylated to overcome its high hydrophobicity (Lig-S) and tested at different concentrations as an emulsifier for stabilizing oil-in-water nanoemulsions. The average diameter of the oil droplets was higher in the nanoemulsion prepared with 0.1 % (w/w) Lig-S (∼380 nm) than those prepared with 0.5 and 1.0 % (w/w) (∼180 nm and ∼170 nm, respectively). Zeta potential measurements predicted the long-term stability of Lig-S nanoemulsion. GC–MS analysis of the volatile carbon compounds derived from the oxidation of soybean oil indicated the highest oxidation rates were in preparations with the smallest droplet size. However, all the Lig-S nanoemulsions showed oxidation rates below the threshold values described in the literature. Microscopy analysis confirmed that all the preparations nanosized, dispersed spherical droplets. Collectively, this study has demonstrated that modified lignin isolated from sugarcane bagasse is an excellent emulsifier for the production of oil-in-water nanoemulsions that have both high physical and oxidative stability, providing prospects for the development of nanosystems, based on sustainable strategies, that can be explored for applications such as entrapment and delivery of hydrophobic or bioactive molecules.
Keywords: Biorefinery; Emulsifier; Lignin; Nanoemulsions; Sugarcane bagasse